2018
DOI: 10.1159/000487728
|View full text |Cite
|
Sign up to set email alerts
|

ShenFu Preparation Protects AML12 Cells Against Palmitic Acid-Induced Injury Through Inhibition of Both JNK/Nox4 and JNK/NFκB Pathways

Abstract: Background/Aims: Nonalcoholic steatohepatitis includes steatosis along with liver inflammation, hepatocyte injury and fibrosis. In this study, we investigated the protective role and the potential mechanisms of a traditional Chinese medicine ShenFu (SF) preparation in an in vitro hepatic steatosis model. Methods: In palmitic acid (PA)-induced murine hepatic AML12 cell injury, effects of SF preparation on cellular apoptosis and intracellular triglyceride (iTG) level were assessed using TUNEL and TG Colorimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…siRNA-mediated NOX4 silencing reduces ROS generation, p38 expression and ERK1/2 phosphorylation level in HUVECs, thus retarding TNF-α-induced oxidative stress and inflammation in AS [ 44 ]. In palmitic acid (PA)-induced murine hepatic AML12 cells, treatment with the JNK inhibitor SP600125 decreases NOX4 expression [ 45 ]. Inhibition of NOX4 and inactivation of JNK helped to mitigate the inflammatory response in fibroblast-like synoviocytes, exerting protective effects against the progression of rheumatoid arthritis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…siRNA-mediated NOX4 silencing reduces ROS generation, p38 expression and ERK1/2 phosphorylation level in HUVECs, thus retarding TNF-α-induced oxidative stress and inflammation in AS [ 44 ]. In palmitic acid (PA)-induced murine hepatic AML12 cells, treatment with the JNK inhibitor SP600125 decreases NOX4 expression [ 45 ]. Inhibition of NOX4 and inactivation of JNK helped to mitigate the inflammatory response in fibroblast-like synoviocytes, exerting protective effects against the progression of rheumatoid arthritis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we established two distinct-mechanical NASH in vitro models by exposing AML12 cells to PA or MCD medium plus LPS and one in vivo model by feeding MCD diet to C57BL/6J mouse for 5 weeks. PA, accounting for 20-30% of total fatty acids in the human body (Carta et al, 2017) and the cause of lipotoxicity in hepatocytes, is widely used to establish NASH in vitro models (Ji et al, 2018). Deprivation of methionine and choline is known to cause many disturbances in hepatic lipid metabolism due to the decreased availability of methionine and choline for phospholipid synthesis (Rinella et al, 2008;Pickens et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with SBT or Stig did not affect the pH values of the culture medium ( Supplementary Figure S2 ), indicating that there were no changes in conditions of the culture medium or stable conditions of the SBT or Stig-added medium. Furthermore, several reports have suggested that SBT and Stig exert beneficial effects in various long-term experiments [ 22 , 78 , 79 , 80 , 81 , 82 , 83 ]. Thus, we presuppose that SBT or Stig may be stably maintained in the culture medium.…”
Section: Discussionmentioning
confidence: 99%